2004
DOI: 10.1038/nn1332
|View full text |Cite
|
Sign up to set email alerts
|

Par6α signaling controls glial-guided neuronal migration

Abstract: Neuronal migrations along glial fibers provide a primary pathway for the formation of cortical laminae. To examine the mechanisms underlying glial-guided migration, we analyzed the dynamics of cytoskeletal and signaling components in living neurons. Migration involves the coordinated two-stroke movement of a perinuclear tubulin 'cage' and the centrosome, with the centrosome moving forward before nuclear translocation. Overexpression of mPar6alpha disrupts the perinuclear tubulin cage, retargets PKCzeta and gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
275
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(297 citation statements)
references
References 49 publications
17
275
1
Order By: Relevance
“…45,49 We found that PDK1 ablation reduces the amount of polymerized microtubules in the developing brain, supporting the idea that the PDK1-Akt pathway regulates locomotion at the level of microtubules. 24 Given that microtubule dynamics is regulated by microtubule-associated proteins that either stabilize or destabilize microtubules, 1,11 we sought to understand the molecular mechanisms that link Akt activation and microtubule regulation by focusing on microtubule-associated proteins.…”
Section: The Pdk1-akt Pathway Regulates Cytoplasmic Dynein/dynactin Csupporting
confidence: 76%
“…45,49 We found that PDK1 ablation reduces the amount of polymerized microtubules in the developing brain, supporting the idea that the PDK1-Akt pathway regulates locomotion at the level of microtubules. 24 Given that microtubule dynamics is regulated by microtubule-associated proteins that either stabilize or destabilize microtubules, 1,11 we sought to understand the molecular mechanisms that link Akt activation and microtubule regulation by focusing on microtubule-associated proteins.…”
Section: The Pdk1-akt Pathway Regulates Cytoplasmic Dynein/dynactin Csupporting
confidence: 76%
“…Previous studies in cell culture have suggested that aPKC activity is required for cellular migration in multiple cell-types by regulating cytoskeletal remodeling (Etienne-Manneville and Hall, 2001;Etienne-Manneville and Hall, 2003;Petit et al, 2005;Sanz-Navares et al, 2001;Solecki et al, 2004). We predicted that the cell patterning phenotypes in has mutants might be due to intrinsic defects in post-mitotic cell migration.…”
Section: Retinal Migration and Cell-type Positioningmentioning
confidence: 78%
“…[158][159][160] This decoupling of the centrosome from the nucleus appears to be due to loss of a specific microtubule bundle known as the microtubule fork/ cage, which connects the two organelles together, 158,159 and is essential for nuclear migration. 161 Disruption of this structure and therefore nucleuscentrosome coupling may be one means by which LIS1/NDEL1 knockdown inhibits nuclear migration.…”
Section: Lis1 Ndel1 Nde1 and Disc1mentioning
confidence: 99%